Anemia and associated factors among HIV/AIDS patients treated with antiretroviral therapy at Mizan-Tepi University Teaching Hospital, Southwest Ethiopia - Tadesse Adula Duguma; Teshale Worku; Mengistu Abayneh (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Human immunodeficiency virus (HIV) and treatments given to HIV patients to reduce complications and fast disease progression, cause a series of hematological abnormalities. Anemia is among hematologic manifestations commonly observed in HIV-positive persons on treatments, initiated by multiple factors. This study aimed to determine the prevalence of anemia and associated factors among patients on highly active antiretroviral therapy (HAART) at Mizan-Tepi University Teaching Hospital from June to September 2021.